Inventory of Main Standards and Parameters of the E Waterway Network - Nations Unies (United Nations, 2013)
This book presents a regularly updated inventory of existing and envisaged standards and parameters of E waterways (Pan-European network of inland waterways of international importance) and ports in Europe and shows, on an internationally comparable basis, the current inland navigation infrastructure parameters as compared to the minimum standards and parameters prescribed in the European Agreement on Mainland Inland Waterways of International Importance (AGN). It identifies bottlenecks and missing links in the existing E waterway network. This second revised edition has just been prepared in accordance with the instructions of member states, both Contracting Parties to the AGN and those not yet Contracting Parties.